Bleeding due to a Broken Heart Valve: Heyde’s Syndrome Secondary to Severe Mitral Regurgitation - Bibek Saha; Jenny J. Cao; Kayla Finnegan; Darine Daher; Allison Reinhardt; Bright Thilagar (Gastro Hep Advances, 2025)
Heyde’s syndrome (HS) is classically characterized by the unique relationship between severe aortic stenosis and gastrointestinal bleeding (GIB) from angiodysplasia. Specifically, the shear stress from valvular disease results in acquired von Willebrand syndrome due to destruction of high-molecular-weight multimers. We present a rare case of HS resulting from severe mitral regurgitation (MR). A 75-year-old male with severe MR was hospitalized twice in a 4-month period for GIB from duodenal angiodysplasia. He was found to have acquired von Willebrand syndrome and managed endoscopically. HS should be in the differential diagnosis for recurrent GIB, especially in the setting of concomitant severe MR.